2000
DOI: 10.1152/jappl.2000.89.4.1340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-hydroxy-β-methylbutyrate on muscle damage after a prolonged run

Abstract: This study examined the effects of supplemental beta-hydroxy-beta-methylbutyrate (HMB) on muscle damage as a result of intense endurance exercise. Subjects (n = 13) were paired according to their 2-mile run times and past running experience. Each pair was randomly assigned a treatment of either HMB (3 g/day) or a placebo. After 6 wk of daily training and supplementation, all subjects participated in a prolonged run (20-km course). Creatine phosphokinase and lactate dehydrogenase (LDH) activities were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 25 publications
2
102
1
8
Order By: Relevance
“…Physical activity alters the enzyme's activity in athletes and the Lactate dehydrogenase is one among the enzyme that present in blood and it is used to monitor the training status of athletes [15,16,21,25]. LDH enzyme level is increased during muscular damage/non-functional overreaching state which can lead to a reduced physical performance [14,19]. The molecular level changes that increase LDH level is the myofibrillar damage in particular sarcomeric Z-disk disruption [13].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity alters the enzyme's activity in athletes and the Lactate dehydrogenase is one among the enzyme that present in blood and it is used to monitor the training status of athletes [15,16,21,25]. LDH enzyme level is increased during muscular damage/non-functional overreaching state which can lead to a reduced physical performance [14,19]. The molecular level changes that increase LDH level is the myofibrillar damage in particular sarcomeric Z-disk disruption [13].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the type of exercised used in the study design, fourteen used RT, three studies performed both aerobic and RT (PORTAL, ZADIK, RABINOWITZ et al, 2011;O'CONNOR and CROWE, 2003;VUKOVICH, STUBBS, BOHLKEN, 2001) and two studies used the aerobic training (downhill) (NUNAN, HOWATSON and VAN SOMEREN, 2010;KNITTER, PANTON, RATHMACHER et al, 2000). There were three studies using aerobic training plus HMβ supplementation (presented in this review): two studies suggested that HMβ supplementation might prevent muscle damage in strenuous aerobic exercise (KNITTER, PANTON, RATHMACHER et al, 2000) and improve lean mass and strength gains (PORTAL, ZADIK, RABINOWITZ et al, 2011), however, these effects does not seem to occur in elite athletes (O'CONNOR and CROWE, 2003).…”
Section: Exercise Type and Effects On Skeletal Musclementioning
confidence: 99%
“…Panton et al 17 e Knitter et al 18 reportaram redução nas concentrações plasmáticas de creatina cinase (CK) e lactato desidrogenase (LDH), que são indicadores de danos na membrana muscular, assim como diminuição da excreção urinária de 3-methil-histidina (3-MH) durante o treinamento, o que indica menores taxas de proteólise.…”
Section: Efeitos Do Hmb Em Indivíduos Iniciando O Programa De Treinamunclassified